The Relationship between employee involvement, psychological empowerment, and attitude towards organizational change in Malaysian Government-Linked Companies (GLCs) / Muhammad Afif Abdul Ghafar - Abdul Ghafar, Muhammad Afif (Institute of Graduate Studies, UiTM, 2017)
This research examined how employees in Malaysian GLCs perceived employee involvement, as well as their attitude towards organizational change. In addition, the relationship between employee involvement, psychological empowerment, and attitude towards organizational change was also examined. A mediation model was derived to further test whether psychological empowerment mediated the relationship between employee involvement and attitude towards organizational change. A convenience sample of employees was attained from seven Malaysian GLCs located across the Klang Valley. These GLCs were involved in a diverse range of industries which includes banking, telecommunication, utility, construction, plantation and automotive. A survey questionnaire which consisted of a (1) demographic profile, (2) Power, Information Sharing, Performance- Based Rewards, and Training Scale (PISPT), (3) Psychological Empowerment (PE) Scale, and (4) Attitude towards Change (ATC) Scale, was used to collect data. With a usable sample size of 313, it was found through descriptive statistics that overall, the employees in Malaysian GLCs had a positive perception of employee involvement and also attitude towards organizational change. Through inferential statistics in the form of correlation, regression, and bootstrapping method, the empirical results provided strong support for the positive relationship between employee involvement, psychological empowerment, and attitude towards organizational change…